Interest premium and external position: A time varying approach - István Kónya; Franklin Maduko (Hungarian Academy of Sciences, Institute of Economics, 2018)
The paper reexamines the empirical relationship between external indebtedness and the interest premium on government bonds. We use a broad sample of countries between 1980-2017 that includes advanced, emerging and less-developed economies. We show that the relationship is strongly state-dependent, and it varies both with the international financial climate, and with the level of development. Moreover, while we find some evidence for non-linearity, this is mostly driven by turbulent periods. We carry out a number of robustness exercises, which highlight issues related to sample composition, the choice of the debt measure, and the definition of crisis events.
Keywords: F34; F41; E43; E44; 330; interest premium; net foreign assets; estimation; country panel; state dependence